Preparation of functionally graded bioceramic coatings - Wang, Ying. (2009)
Functionally graded materials (FGM) are materials that have a compositional gradient and property variation from the surface to the interior of the materials. This report presents the preparation of three functionally graded coating (FGC) systems. The aim of these FGCs is to provide improved reliability, bioactivity and biocompatibility that are the most desired features for biomedical implants. The FGC systems based on (1) various particle size ranges of spherical hydroxyapatite (SHA); (2) tricalcium phosphate (TCP)/HA; and (3) titania (Ti02)/HA are investigated. The coatings are graded in accordance to adhesive strength, bioactivity and biocompatibility. The bond coat on the Ti-6A1-4V substrate is deposited with materials that would provide high adhesive strengths. The top coat is composed of calcium phosphate compounds that would provide high bioresorbability (TCP/HA FGCs) or high biocompatibility (SHA and Ti02/HA FGCs).